Analisis Nilai-Nilai Pendidikan Dalam Konteks Menjadi Pendidik Profesional - Dini Gita Sartika; Ayu Lestari; Puja Hayati; Salsa Bila Khotrun Nada; Wismanto Wismanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
A teacher is a person who is admired and imitated, his actions, words and even thoughts always become part of the culture of the people around him. However, not everyone develops the skills and abilities to become a teacher. The purpose of this research is to find out how to become an educator based on the Al-Qur'an and Hadith to become an example for others as shown by Rasullullah. And as an educator in the school family environment and in the community. Because the role of educators is very important for the nation's next generation, especially for the progress of the country, so that they are not left behind in terms of technology, science and religion. Because religion is an indispensable foundation for this world and the hereafter. This study used qualitative research methods. In this method, researchers can use interviews, observations, and content analysis to understand the perspectives, attitudes, and values held by teacher educators regarding education. The results of this research show that there are several hadiths of the Prophet Muhammad, and several surahs of the Koran, including Surah Al-Baqarah/2: 129 concerning the sending of an educator (Rasulullah ). Allah sent a Messenger from among the descendants of people who were famous in appearance and pedigree. He is the one who guides humans from error to light and guides them to the straight path. The fields of education that are the responsibility of every teaching staff are physical, spiritual and character education.